IMPORTANCE OF CONTROLLING THE STRESS IN THE VALIDATION OF BIOLOGICAL RESULTS - Chies, A. B.; Pereira, OCM (Interciencia, 1995)
The stress syndrome includes ample phenomena, characterized by complex neuroendocrinological alterations. Such alterations, in the long run, give rise to important modifications in reply of different organs and tissues to diverse agonists, specially sympathicommentic. These alterations, at least partially, are part of an ''adjustment mechanism'' of the tissues. Thus this possibility of obtaining altered responses in function of stress leads to the need of special care in the prevention and control of stressogenic stimuli in the process of research. Taking cave of preventing stressogenic stimuli, it becomes possible to determine a profile of trustworthy replies, considered as standard From such reply standards, toe can know more clearly what is a ''normal'' response or what is a response ''altered'' by some factor, specially stress.